Effect of Electroacupuncture Prestimulation with Mental Tri-Needles on the Inflammatory Response of Hippocampus in Aged Rats with Perioperative Neurocognitive Disorders - WANG Xiangfeng; HUANG Jinyan; LIU Wei; LUO Huiqin; WANG Guanhui; LIN Qin; CHEN Bin (康复学报)
ObjectiveTo observe the effect of electroacupuncture (EA) prestimulation with mental tri-needles on the inflammatory response of hippocampus in aged rats with perioperative neurocognitive disorders (PND).MethodsA total of 24 aged male SD rats were randomly divided into control group, anesthesia group, operation group and acupuncture group, with 6 cases in each group. The acupuncture group received EA prestimulation with mental tri-needles, and the other groups didn't receive any intervention. The aged PND rat model was established by intramedullary nailing surgery for femoral neck fracture in the operation group and the acupuncture group. Open field experiment and water maze test were used to evaluate the cognitive function; ELISA method was used to detect interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α in the plasma; HE staining was used to observe the cell morphology of hippocampal tissue; TUNEL staining was used to observe the apoptosis of hippocampal tissue; Western blot and real-time fluorescence quantitative PCR were used to detect the protein content and mRNA expression of IL-1β, IL-6 and TNF-α in hippocampal tissue.Results(1) Cognitive function: compared with the control group and the anesthesia group, the time of staying in the central quadrant, the number of crossings of the quadrant, the number of standing ups, the total distance of swimming, the swimming speed and the number of platform crossings in the operation group significantly decreased, and the latency and the time of staying in the target quadrant were significantly prolonged (P<0.05); compared with the operation group, the time of staying in the central square, the number of crossings of the quadrant, the number of standing ups, the total distance of swimming, the swimming speed and the number of platform crossings in the acupuncture group significantly increased, and the latency and the time of staying in the target quadrant were significantly shortened (P<0.05). (2) Levels of IL-1β, IL-6 and TNF-α in plasma: compared with the control group, the levels of IL-1β, IL-6 and TNF-α significantly increased in the anesthesia group, operation group and acupuncture group (P<0.05); compared with the anesthesia group, the levels of IL-1β, IL-6 and TNF-α in the operation group significantly increased (P<0.05); compared with the operation group, the levels of IL-1β, IL-6 and TNF-α in the acupuncture group significantly decreased (P<0.05). (3) Morphology and apoptosis of hippocampal neurons: the most sever injury of hippocampal neurons occured in the operation group, showing as interstitial edema and a small amount of glial cell proliferation, while the injury of hippocampal neurons was slight and the morphology was relatively normal in the acupuncture group. Compared with the control group and the anesthesia group, the percentages of apoptotic cells in the hippocampus of the operation group and the acupuncture group significantly increased (P<0.05); and compared with the operation group, the percentage of apoptotic cells in the hippocampus of the acupuncture group significantly decreased (P<0.05). (4) Protein contents and mRNA levels of IL-1β, IL-6 and TNF-α in hippocampus: compared with the control group and the anesthesia group, the protein contents and mRNA levels of IL-1β, IL-6 and TNF-α in the operation group significantly increased (P<0.05); compared with the operation group, the protein expression of IL-1β, IL-6 and TNF-α and their mRNA levels in the acupuncture group significantly decreased (P<0.05).ConclusionEA prestimulation with mental trineedles can reduce the injury and apoptosis of hippocampal cells in aged rats with PND, and improve cognitive function, which may be related to the inhibition of the overexpression of IL-1β, IL-6 and TNF-α in the hippocampus of aged rats and reducing the inflammatory reaction in brain tissue.